Labour market participation changes analysis: An application to Monterrey metropolitan area's case - Valero Gil, Jorge N. (Estudios Económicos de El Colegio de México, 1997)
This paper analyzes changes in labor force participation in the Metropolitan Area of Monterrey, Mexico, between 1976 and 1996. A life cycle model is used to decompose the changes in participation rates into parametric and evolutionary changes. The fall in real wages in Monterrey during this period is modelled as an unexpected change and the effect on the marginal utility of wealth is considered. We want to know whether it is possible to make predictions about labor force participation using observed variables, i.e., inelastic evolutionary changes, and whether the elasticity of labor supply is as in this model has been found in studies using other models.